A NEED ANALYSIS OF LEARNING ENGLISH FOR COMPUTER SCIENCE STUDENTS - Netty Huzniati Andas; Karman Karman; Muliyadi Muliyadi (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2021)
English learning materials for Computer Science Department students which are suitable with learners’ needs are scarcely available. Thus, a study on analysis of students’ need is necessary. The purpose of this study was to find out students’ need on English based on ESP approach of Computer Science Study Program at USN Kolaka. This study used need analysis with survey design. The instruments used in this study were a semi-close ended questionnaire and interview. The questionnaire was distributed to 50 respondents and four students were interviewed. All of them were from Computer Science students at Universitas Sembilanbelas November Kolaka. It was found out that the students’ goal to learn English is to compete in the world of work. The expected level of English is advanced level. The priority skills are speaking and reading skills focusing on vocabularies related to computer science. In speaking skill activity, most students prefer to make a dialogue and then practice with friends. Meanwhile, in reading skills, students prefer activities that train their understanding and concentration like answering questions from a reading text.